Mapping Islamic Entrepreneurship in Integrating Religious Values With Business Principles - Yohanna, Larisa; Masayu Endang Apriyanti; Bondan Dwi Hatmoko (International Journal of Law Social Sciences and Management, 2025)
Islamic entrepreneurship links entrepreneurial activities with Islamic values ​​and principles, which aim to improve the welfare of individuals and society. This study aims to investigate how religious values ​​and business principles can be integrated in Islamic entrepreneurship research through a bibliometric mapping approach. Data were collected from the Scopus database with selected journal articles that met predetermined inclusion and exclusion criteria, then processed using R Studio (Biblioshiny). This bibliometric analysis highlights the potential for interdisciplinary collaboration and cross-comparison that can broaden the understanding and practice of Islamic entrepreneurship in an increasingly global world. Using a variety of bibliometric techniques, this study reveals existing patterns and trends, and highlights key themes, influential authors, and emerging trends. The results of this analysis are then interpreted in the context of the broader literature on entrepreneurship and Islamic studies, with the aim of contributing to the development of knowledge through a systematic analysis of the structure and development of this field. Although the topic of Islamic entrepreneurship continues to grow, there is a need to deepen the exploration of Sharia Compliance, Earning Management, and related themes such as Social Entrepreneurship and SMEs. Increasing international collaboration and cross-cultural research will enrich insights into integrating Islamic values ​​with modern entrepreneurial practices, creating new opportunities for the development of more sustainable and applicable Islamic entrepreneurship.